Studi Tingkah Laku Makan dan Berkubang Kerbau Lumpur (Bubalus bubalis carabanesis) di Desa Teluk Kayu Putih - Nining Nuraida; Try Susanti (Jurnal Biosilampari : Jurnal Biologi, 2024)
This study is to investigate the feeding and washing habits of swamp buffaloes (Bubalus bubalis carabanesis) in Teluk Kayu Putih Village, VII Koto District, Tebo Regency. This study was carried out from July to October 2023, involving a sample of 5 buffalo. The sample included adult male and female buffalo, as well as immature male and female buffalo (referred to as "girl"), and male calves. This study employs the One Zero technique, utilizing 10-minute intervals, conducted between 06:00 and 16:00 WIB. The research findings indicated that adult female buffalo exhibited the most feeding activity, specifically 16.36 times, whereas male buffalo calves shown the lowest feeding activity, specifically 9.00 times. The frequency of rumination, a type of ruminant behavior, was highest in young males at a rate of 7.42 times, whereas young female buffalo exhibited the lowest frequency of rumination at 5.93 times. The study revealed that adult male buffalo engage in wallowing activity more frequently than any other group, with an average of three times per day. In contrast, cub males engage in wallowing behavior just once per day, which is the lowest frequency seen. The average duration of wallowing was determined to be 37.33 minutes.